2003
DOI: 10.1007/s00122-002-1085-z
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of gene flow and differential geographical structure of molecular diversity in wild and domesticated common bean (Phaseolus vulgaris L.) from Mesoamerica

Abstract: Using amplified fragment length polymorphisms (AFLPs), we analyzed the genetic structure of wild and domesticated common bean (Phaseolus vulgaris L.) from Mesoamerica at different geographical levels to test the hypothesis of asymmetric gene flow and investigate the origin of weedy populations. We showed both by phenetic and admixture population analyses that gene flow is about three- to four-fold higher from domesticated to wild populations than in the reverse direction. This result, combined with other work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
211
6
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(240 citation statements)
references
References 29 publications
18
211
6
5
Order By: Relevance
“…This single domestication model showed similar posterior probabilities for the two gene pools. These results support hypotheses proposed in common bean by previous researchers Papa and Gepts 2003;Rossi et al 2009). The parameters estimated here suggest a short duration with a large founding population.…”
Section: A Model For Domestication In Common Beansupporting
confidence: 93%
See 3 more Smart Citations
“…This single domestication model showed similar posterior probabilities for the two gene pools. These results support hypotheses proposed in common bean by previous researchers Papa and Gepts 2003;Rossi et al 2009). The parameters estimated here suggest a short duration with a large founding population.…”
Section: A Model For Domestication In Common Beansupporting
confidence: 93%
“…Statistically significant differences are indicated: *, P < 0.05; **, P < 0. and 0 in Andean). This a strong indicator of gene flow and is consistent with the earlier results by Papa and Gepts (2003) and Papa et al (2005) for common bean, as well the bidirectional gene flow observed in 12 of the 13 most important food crops (Ellstrand et al 1999;Stewart et al 2003). Moreover, for 7 of these 13 crops, introgression of domesticated traits increased the competitiveness of the related weed species (Ellstrand et al 1999;Ellstrand and Schierenbeck 2000).…”
Section: A Model For Domestication In Common Beansupporting
confidence: 90%
See 2 more Smart Citations
“…The fact that isolation by distance was detectable only when considering a large spatial scale may indicate that gene flow is more important than drift in these two parasitoid species and that the chance of local adaptation will be limited. Interestingly, absence of isolation by distance in cultivated beans and associated bruchid beetles has previously been explained by frequent long-distance transportation by humans of beans for consumption (Gepts 1998;Papa & Gepts 2003;Alvarez et al 2007). However, this explanation can be ruled out in our system, as the two parasitoids attack either eggs or second instar larvae (Cave 1995), which are only found on immature plants.…”
Section: Discussionmentioning
confidence: 99%